Pengabdian Masyarakat Olahan Cumi Sambel Ijo, Menu Keluarga Sehat, Sebagai Peluang Usaha Rumahan di RT.04 Kelurahan Pantai Amal - Nurul Hidayat; Monika Martiyoli Urei; Yustinus Jemy; Eka Wulandari; Rehan Aldi Saputro; Rindiani; Susan Nur Fadilla (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This community service activity aims to introduce the innovation of processed sambel green squid as an alternative to a healthy family menu based on local potential in RT 4, Pantai Amal Village. This program is carried out through a participatory approach by involving housewives in training, preparation, and nutrition education related to processed squid. The results of the activity showed an increase in participants' knowledge and skills in processing squid into nutritious, hygienic, and visually appealing dishes. In addition to providing health benefits, this innovation also opens up home business opportunities that support family food security. By making optimal use of local marine products, this program strengthens the economic and nutritional value of the daily consumption of coastal communities.